EKSISTENSI KOSMETIK BERLABEL HALAL PADA MASYARAKAT MUSLIM, DAN NON-MUSLIM (STUDI KASUS WARDAH KOSMETIK) - Imas Masitoh (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The halal lifestyle has recently swept the world, including Indonesia, oneofthe halal products that have developed in Indonesia is cosmetic products. This phenomenon has an impact on increasing the purchase of halal cosmetics. With more and more cosmetic companies emerging in Indonesia, the competition in the cosmetics business is getting tougher. To be able to win the competition so as not to lag behind consumers, manufacturers must do several ways to keep a product at the market leader even though many other cosmetics are rivals. The purpose of this study is to find out what factors make halal cosmetic products remain the market leader even though many other cosmetics are rivals. This research uses qualitative descriptive analysis with a phenomenological approach, literature studies use secondary data obtained through scientific articles and other related documents. The results of this study found that there are several factors that make halal cosmetics remain the choice of the Muslim community and non-Muslim communities, namely quality, service and affordable prices.